Estudio de factibilidad para la creación de una Caja de Ahorro para los socios del Consorcio de Transportistas Urbanos Ciudad de Loja - López Jiménez, Jina Lisbeth (2024)
The importance of saving banks lies in the opportunity for improvement and economic solidity for those with unstable economic income or limited access to traditional banking, and they also promote a thrifty culture. Thus, the general objective of the research work was to evaluate the feasibility of creating a savings bank for the members of the Transport Consortium of the city of Loja In order to accomplish this, research with an exploratory scope was used, and a mixed approach through the processing and analysis of data, the design used was transversal; in addition, bibliographic collection techniques were used; likewise, the application of 238 surveys to the consortium partners and an interview to the consortium's officers. Once the positions and preferences of the members had been established, the results of the market study showed that 79% of the savings bank's creation was acceptable; the technical study established the ideal location for the savings bank; and the legal administrative study established the regulations for the savings bank. Finally, the financial evaluation establishes initial investment amounts of USD 16,168.00, which is recovered in 3 years, seven months, and 27 days; in addition, the calculation of the evaluation criteria, where the NPV is located in USD 16,048.20; the RCB shows that 0.01 cents is obtained for each dollar; likewise, the IRR percentage is 33.39% above the AARR of 10.52%; and, the sensitivity analysis will support changes in the face of a 0.41% increase in costs and a 0.40% decrease in income. In conclusion, the proposal to create a savings bank for this sector is feasible.